Introduction to Field-Being Philosophy : An Anthology of Lik Kuen Tong's Thought - Dykeman, Therese Boos; Weed, Laura E. (Cambridge Scholars Publishing, 2022)
This text is the first concise anthology of Lik Kuen Tong's Field-Being philosophy. In addressing the ontology of both Eastern and Western thought, Field-Being philosophy offers a new metaphysics. Inclusively, it makes room at the table of philosophy for indigenous philosophy, and, foundationally, it rethinks the universe and the global world ontologically as ""activity"" and ""relationality."" A comprehensive philosophy, it considers what is as movement, as well as the what of movement, and inventively adds the concept of ""betweenness."" This philosophy of movement or ""activity,"" being fut.